Impact of AGOA on Agricultural Exports Growth of Member Countries: A Dynamic Shift-Share Analysis - Yeboah, Osei; Shaik, Saleem; Musah, Jamal (Journal of Applied Business and Economics, 2021)
Since the commencement of AGOA, U.S. exports to Sub-Saharan Africa (SSA) have grown by 23% attaining $21 billion while the exports from the U.S. to the rest of the world increased by only 15%. Total bilateral trade between the U.S. and SSA also increased by 5.8%, up from $36.9 billion in 2015 to $39 billion in 2017. U.S. imports from SSA region have also increased more than three times reaching $26.7billion in 2014. However, others have argued that AGOA has failed to enhance member countries’ agricultural exports to the U.S. But these studies only focused on overall export growth. Using dynamic shift-share analysis, this study evaluates potential impact of AGOA on U.S. export growth for four major aggregate commodity groups – bulk, consumer, intermediate and ag-related. Export performance is empirically examined by comparing pre-AGOA (1980-200), post-AGOA (2000-2019) and complete time-period (1980- 2019). The results suggest member countries’ exports have grown from a deficit of $436 million pre-AGOA to $1,487 million in Post-AGOA with bulk commodities contributing close to 50%.